Infarction in middle cerebellar peduncle caused by ipsilateral vertebral artery hypoplasia - Verma, Archana; Kumar, Alok (International Journal of Research in Medical Sciences, 2023)
AICA (anterior inferior cerebellar artery) is a ramification of the basilar artery. It originates in the lower or middle third of the basilar artery at the junction of the medulla oblongata and pons. A young 33-year-old male presented with an unsteady gait, left-sided facial hypoesthesia, and hearing impairment on the left side. On neurological evaluation, he was found to have left-sided sensorineural deafness and signs of incoordination. A brain magnetic resonance image (MRI) was suggestive of an acute infarct in the left middle cerebellar peduncle and a hypoplastic left vertebral artery recognized on MRA. We presented a case report wherein a patient presented with clinical features of a middle cerebellar peduncle infraction caused by hypoplasia of the left vertebral artery.